Prospecting the First Chilean Martian Simulants from the Atacama Desert for Isru and Potential Applications - Alam-, M (Academic Press, 2025)
Martian simulants are an essential part of in situ resource utilization (ISRU) technology development and testing, and aid in providing new astrobiology insights regarding Mars s past habitability. This study proposes a new method involving average and standard deviation (ASD), complementary to figure of merit (FOM) simulant evaluation methods, for geochemical prospection and evaluation of simulant feedstock using portable XRF (pXRF) and whole-rock (ICP-OES) analyses. It also presents simulant modification calculations (SMC) that integrate multiple approaches used in simulant production and design, and provides theoretical mineral recipes (estimated mineral composition) and their estimated geochemical compositions for FOM evaluation of an intended target composition. These methods were used to prospect simulant material in volcanic-subvolcanic outcrops at the SW edge of the Atacama Desert in Chile, and to evaluate their potential for standard and enhanced simulant development. Through ASD (pXRF data) and FOM (ICP-OES data) evaluation, this resulted in the presentation of the first Chilean basic Martian bedrock simulant that can be used for biomining applications, which is tentatively labeled as Chilean Atacama Desert 1 (CAD-1). An Excel file with the applied prospection method and database is also available for simulant feedstock prospection (Supplementary section). Applying these methods will provide more base materials and components for simulant development and allow flexibility in their design for general and specific applications. © 2024 Elsevier Inc.